Cytokinins and Abscisic Acid Act Antagonistically in the Regulation of the Bud Outgrowth Pattern by Light Intensity - Corot, Adrien; Roman, Hanaé; Douillet, Odile; Autret, Hervé; Perez-Garcia, Maria-Dolores; Citerne, Sylvie; Bertheloot, Jessica; Sakr, Soulaiman; Leduc, Nathalie; Demotes-Mainard, Sabine (Frontiers in Plant Science, 2017)
Bud outgrowth is a key process in the elaboration of yield and visual quality in rose crops. Although light intensity is well known to affect bud outgrowth, little is known on the mechanisms involved in this regulation. The objective of this work was to test if the control of bud outgrowth pattern along the stem by photosynthetic photon flux density (PPFD) is mediated by sugars, cytokinins and/or abscisic acid in intact rose plants. Rooted cuttings of Rosa hybrida ‘Radrazz’ were grown in growth chambers under high PPFD (530 μmol m-2 s-1) until the floral bud visible stage. Plants were then either placed under low PPFD (90 μmol m-2 s-1) or maintained under high PPFD. Bud outgrowth inhibition by low PPFD was associated with lower cytokinin and sugar contents and a higher abscisic acid content in the stem. Interestingly, cytokinin supply to the stem restored bud outgrowth under low PPFD. On the other hand, abscisic acid supply inhibited outgrowth under high PPFD and antagonized bud outgrowth stimulation by cytokinins under low PPFD. In contrast, application of sugars did not restore bud outgrowth under low PPFD. These results suggest that PPFD regulation of bud outgrowth in rose involves a signaling pathway in which cytokinins and abscisic acid play antagonistic roles. Sugars can act as nutritional and signaling compounds and may be involved too, but do not appear as the main regulator of the response to PPFD.